1997
DOI: 10.1006/dbio.1997.8525
|View full text |Cite
|
Sign up to set email alerts
|

FGF-Stimulated Outgrowth and Proliferation of Limb Mesoderm Is Dependent on Syndecan-3

Abstract: The outgrowth of the mesoderm of the developing limb bud in response to the apical ectodermal ridge (AER) is mediated at least in part by members of the FGF family. Recent studies have indicated that FGFs need to interact with heparan sulfate proteoglycans in order to bind to and activate their specific cell surface receptors. Syndecan-3 is an integral membrane heparan sulfate proteoglycan that is highly expressed by the distal mesodermal cells of the chick limb bud that are undergoing proliferation and outgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…For example, chick syndecan-3 expressed in the distal mesenchymal cells underlying the AER plays an important role during limb outgrowth by regulating the interaction of FGFs with the underlying mesoderm (20). On the other hand, our results indicate that 6-O-sulfated structures of HS are preferentially found in the proximal regions of the limb buds.…”
Section: Heparan Sulfate O-sulfotransferases In Chick Limbmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, chick syndecan-3 expressed in the distal mesenchymal cells underlying the AER plays an important role during limb outgrowth by regulating the interaction of FGFs with the underlying mesoderm (20). On the other hand, our results indicate that 6-O-sulfated structures of HS are preferentially found in the proximal regions of the limb buds.…”
Section: Heparan Sulfate O-sulfotransferases In Chick Limbmentioning
confidence: 66%
“…In addition, HSPGs may bind growth factors in the extracellular matrix and thereby alter their stability and modulate their effective concentrations (17)(18)(19). Syndecan-3 (integral membrane HSPG) plays such a role in chick limb outgrowth by controlling the FGF signaling between the AER and mesoderm (20). Glypican-3 (glycosylphosphatidylinositol-anchored cell surface HSPG) controls cellular responses to bone morphogenetic protein-4 (BMP-4) in limb patterning (21).…”
mentioning
confidence: 99%
“…One function is to stimulate the proliferation of cells in the progress zone and thus produce the new cells required for limb outgrowth. Studies employing markers for cell proliferation have directly demonstrated that FGFs are mitogens for limb bud mesenchyme (Aono and Ide 1988;Dealy et al 1997). Moreover, ectopic expression of Fgf2 on the anterior side of the wing bud apparently causes excess proliferation of mesenchymal cells, resulting in abnormal thickening and splitting of the skeletal primordia (Riley et al 1993).…”
Section: Specific Functions Of Fgfs Produced In the Aermentioning
confidence: 99%
“…Antibody Interference Assays in Cultured Chondrocytes-In previous studies by others, antibodies raised against syndecan-3 were used to interfere with its function and determine its role in developmental processes (30). Thus, we used a similar approach to test the role of syndecan-3 in chondrocyte proliferation.…”
Section: Syndecan-3 and Chondrocyte Proliferation In Vivo-mentioning
confidence: 99%